Effects of LaB6 on composition, microstructure and ablation property of the HfC-TaC-SiC doped C/C composites prepared by precursor infiltration and pyrolysis. (15th May 2021) - Fang, Cunqian; Huang, Boyun; Yang, Xin; Shi, Anhong; Zhang, Ze; Yi, Jinren; Huang, Qizhong
Highlights: LaB6 offers the reactive sintering by reacting with HfC or TaC to establish a compact ceramic structure. La2 O3 can react with other oxides to generate several ternary phases of La2 Si2 O7, La2 Hf2 O7 and LaTaO4, resulting in the reconciled layer at the ablation center of composites. Abstract: HfC, TaC and SiC with different proportions were introduced into Cf /LaB6 preform to fabricate four kinds of UHTC doped C/C composites. Results show that LaB6 could react with HfC or TaC to establish a compact ceramic structure. After ablation for 120 s, the composites doped with LaB6 -HfC-TaC-SiC possessed the best ablation property, and the ablation rates were 1.129 mg/s and 3.133 μm/s. A layer with La2 Si2 O7, La2 Hf2 O7 and LaTaO4 is observed due to the reactions between La2 O3 and other binary oxides. Further ablation was suppressed and stability of the multi-phase layer is therefore confirmed, indicating good coordination among the oxides.